Variation in the Efficacy of Anti-Ulcerative Colitis Treatments Reveals the Conflict Between Precipitating Compatibility of Traditional Chinese Medicine and Modern Technology: A Case of Scutellaria-Coptis - Liu, Dan; Zhao, Ran; Wu, Yajing; Wang, Yunhong; Yang, Rongping; Ke, Xiumei (Frontiers in Pharmacology, 2022)
Scutellariae and Coptidis compose a classical drug pair applied in clinical practice to dispel heat, dryness and dampness, and they are also precipitation compatible drug pairs. With modern technology, Scutellaria-Coptis is mostly prepared by decocting its components separately, while in the traditional method, it is predominantly prepared as a combined decoction. The present study investigated the effects and mechanisms of separate and combined application of Scutellaria-Coptis decoction on ulcerative colitis (UC) in mice induced by the administration of dextran sulfate sodium (DSS). Changes in body weight, colon length, and Disease Activity Index scores were also evaluated. Hematoxylin and eosin staining and other methods were used to evaluate the overall condition of animals in each group. Intestinal microflora was analyzed using 16S rRNA sequencing, while colon inflammation and antioxidant capacity were evaluated based on the levels of interleukin-6 (IL-6), IL-10, IL-1β, tumor necrosis factor-α, superoxide dismutase, malondialdehyde, and reduced glutathione. The results revealed that Scutellaria-Coptis significantly relieved colon inflammation in mice, and the combined decoction of Scutellaria-Coptis exerted a significant effect on UC. Notably, the protective effect of Scutellaria-Coptis against colon inflammation was weakened when the antibiotic mixture was partially consumed by the gut microbiota. The results of 16S rRNA sequencing showed that the group treated with combined decoction of Scutellaria-Coptis exhibited a higher intestinal microbial diversity and intestinal flora composition than the separated decoction group. Treatment of mice with UC by administering Scutellaria-Coptis decoction through intestinal flora removal (ABX) and fecal microbial transplantation (FMT) was closely associated with intestinal flora composition. In conclusion, Scutellaria-Coptis can relieve UC with an excellent effect especially when taken as a combined decoction, alleviating colon inflammation incurred by intestinal microbes to a certain extent.